Cutaneous Neuroendocrine Metastases of Visceral Origin Responsive to Surgical Resection and Targeted Radionuclide Therapy - Eleanor Tung-Hahn; Ghassan El-Haddad; Jonathan Strosberg (Hindawi Limited, 2024)
Neuroendocrine neoplasms (NENs) encompass a diverse range of biologically and behaviorally distinct epithelial malignancies that derive from neuroendocrine cells. These neoplasms are able to secrete a variety of bioactive amines or peptide hormones. The majority of NENs are well-differentiated and are defined as neuroendocrine tumors (NETs). While NETs are known to frequently metastasize to lymph nodes, liver, and lungs, spread to the skin is extremely rare and is often a late finding. Because cutaneous metastasis from a visceral site represents distant tumor dissemination, prompt histologic diagnosis is critical in terms of selecting further treatment options and ultimately impacts subsequent prognosis. This report presents a man with painful cutaneous NET metastases initially on the face then scalp. He had a prior history of longstanding and progressive stage IV visceral disease. Multimodal therapy with initial surgical resection of the larger facial lesion and radionuclide infusion therapy was undertaken. Excision fully removed the temple lesion and resolved pain. Peptide receptor radionuclide therapy (PRRT) with 177Lu-DOTATATE, a radiolabeled somatostatin analog that targets somatostatin receptors on NETs, was given along with maintenance lanreotide therapy, which resolved the scalp lesion, prevented recurrence of prior lesions and development of new cutaneous metastases, and controlled his visceral disease. PRRT has not been previously described in the management of cutaneous NET metastases. Due to the rare nature of cutaneous NET metastases, there is no consensus regarding optimal management. As such, we propose novel multimodal therapy involving excision and targeted radionuclide therapy as a possible effective option.